Case report: Cerebral artery air embolism during CT-guided lung nodule resection in hybrid theater - Xing, Huajie; Wang, Zhiqiang; Jiang, Yuequan (Frontiers in Surgery, 2022)
Our goal was to describe a rare case of cerebral artery air embolism during CT-guided lung nodule resection in hybrid theater, with emphasis on prevention and early detection of this life-threatening complication.